2012
DOI: 10.1093/tropej/fms012
|View full text |Cite
|
Sign up to set email alerts
|

A Hospital Policy Change Toward Delayed Cord Clamping is Effective in Improving Hemoglobin Levels and Anemia Status of 8-month-old Peruvian Infants

Abstract: A hospital policy change toward delayed cord clamping is effective in improving Hb levels and the anemia status of 8-month-old infants. Prior to scaling-up this intervention, issues related to training, monitoring, safety, additional long-term benefits and specific local conditions should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…These include higher mean hemoglobin levels, iron stores as well as reduced prevalence of iron deficiency anemia (Gyorkos et al [7]. Milking the umbilical cord five times at birth is also associated with a decreased risk for iron-deficiency anemia (Erickson-Owens et al [8])…”
Section: Introductionmentioning
confidence: 99%
“…These include higher mean hemoglobin levels, iron stores as well as reduced prevalence of iron deficiency anemia (Gyorkos et al [7]. Milking the umbilical cord five times at birth is also associated with a decreased risk for iron-deficiency anemia (Erickson-Owens et al [8])…”
Section: Introductionmentioning
confidence: 99%
“…The sample size calculation is, therefore, based on an expected effect size of 0.2 kg and a SD of 1.01 kg, a significance level (α) of 0.05 and a power (1-β) of 0.80. As informed by a previous study in the same hospital population, 41 the final sample size takes into account a 20% loss to follow-up. Based on the above specifications and a two-sided independent t test, we estimate that 1010 participants is the total sample size needed to declare that infant weight gain is different between intervention groups.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Delayed cord clamping results in increased neonatal haemoglobin and ferritin concentrations after birth, without an increased risk of adverse health outcomes in the mother or infant, aside from some reports of an increased risk of polycythaemia (Hutton & Hassan 2007;McDonald et al 2013). These improvements in iron status and decreased risk of iron deficiency and anaemia last throughout early infancy (Andersson et al 2011;Mercer et al 2018), even to 8-12 months of age (Gyorkos et al 2012;Kc et al 2017). Furthermore, increased brain myelination at 4 months (Mercer et al 2018) and improved fine motor and social development at 4 years, but not 1 year (Andersson et al 2014;Andersson et al 2015), has been reported in infants randomised to delayed clamping.…”
Section: Delayed Clamping Of the Umbilical Cordmentioning
confidence: 99%